The Effects of Acupuncture on Cancer-Related Fatigue: Updated Systematic Review and Meta-Analysis - Jang, Andrew (Integr Cancer Ther, 2020)
BACKGROUND: Several studies have identified fatigue as one of the major symptoms experienced during and after cancer treatment. However, there are limited options to manage cancer related fatigue (CRF) with pharmacological interventions. Several acupuncture studies suggested that acupuncture has a positive impact on CRF. This review aims to assess the evidence of acupuncture for the treatment of CRF. METHOD: Electronic database searches were conducted on 4 English databases (Medline, PubMed, Embase, and ScienceDirect). Search keywords were; “acupuncture” and “cancer,” or “cancer related fatigue.” Studies published as full text randomized controlled trials (RCTs) in English were included. Estimates of change in fatigue cores were pooled using a random effects meta-analysis where randomized comparisons were available for true acupuncture versus sham acupuncture and true acupuncture versus usual care. The quality of original papers were assessed using the Cochrane Collaboration’s tool for assessing risk of bias (ROB). RESULTS: Nine RCTs were selected for review with a total of 809 participants and a range of 13 to 302 participants within the studies. Six RCTs reported significant improvement of CRF for the acupuncture intervention compared to the control groups. Pooled estimates suggest Brief Fatigue Inventory scores are 0.93 points lower 95% CI (−1.65, −0.20) in true acupuncture versus sham acupuncture and 2.12 points lower 95% C (−3.21, −1.04) in true acupuncture versus usual care. Six studies had low risk of bias (ROB) and 3 studies had a moderate ROB predominantly in blinding of participants, blinding of assessors and incomplete data outcomes. Among the 9 RCTs, 2 studies have reported the occurrence of minor adverse effects (spot bleeding and bruising) related to acupuncture treatment. No serious adverse reactions related to acupuncture were reported. CONCLUSION: The current literature review suggests that acupuncture has therapeutic potential in management of CRF for cancer survivors. Promotion of acupuncture in cancer care to manage CRF may improve the quality of life of cancer survivors.